Search 75,981 tutors
FIND TUTORS
Ask a question
0 0

6/(x+4) - 2/(x-3) = 3

Tutors, please sign in to answer this question.

3 Answers

Your common denominator is (x+4)(x-3). If you multiply your rational equation by this denominator you will come up with the following equation:

                                   6(x-3) -2(x+4) = 3(x-3)(x+4)  or (after simplifications)

                                          3x^2 -x - 10 = 0  

We cabn factor this equation. It gives us     (3x +5)(x-2) = 0. Thus, your solutions are

                                                      x = -5/3     and x=2

multiple (x+4)(x-3)on both sides. We get 6*(x-3)-2*(x+4)=3*(x+4)*(x-3) The equation is 6x-18-2x-8=3(x2-3x+4x-12) we get: 4x-26=3x2+3x-36 x=2 or x= -5/3